2006
DOI: 10.1016/j.jcrs.2006.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Late spontaneous in-the-bag intraocular lens and capsular tension ring dislocation in pseudoexfoliation syndrome

Abstract: Two patients with pseudoexfoliation syndrome (PEX) in whom late spontaneous in-the-bag intraocular lens (IOL) and capsular tension ring (CTR) dislocation occurred 3 and 6 years after cataract surgery are described. The patients received CTRs because of phacodonesis due to zonular laxity. The IOLs were centered postoperatively, and there was no postoperative ocular trauma. In both cases, removal of the IOL and CTR within the capsular bag was performed uneventfully by a scleral tunnel incision and an anterior ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 15 publications
1
16
0
2
Order By: Relevance
“…Creep is usually increased by temperature. Several studies have shown standard PMMA CTRs failing to prevent capsular bag shrinkage or late dislocation [6][7][8][9]. Capsular shrinkage and dislocation is known to be multi-factorial, being influenced by: progression of zonular damage, fibrous metaplasia of residual lens epithelial cells, IOL material and insufficient resistance to compression by the CTR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Creep is usually increased by temperature. Several studies have shown standard PMMA CTRs failing to prevent capsular bag shrinkage or late dislocation [6][7][8][9]. Capsular shrinkage and dislocation is known to be multi-factorial, being influenced by: progression of zonular damage, fibrous metaplasia of residual lens epithelial cells, IOL material and insufficient resistance to compression by the CTR.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the force exerted by the CTR, several cases of capsular bag shrinking have been published, some of them leading to capsular bag-IOL-CTR complex dislocations [6][7][8][9]. In this study we have measured the deformation of a CTR when submitted to a certain pressure "in vitro" and to ascertain if commercially available CTR's remain within the elastic region when the compression is maintained overtime.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Some surgeons advocate large capsulorrhexis and capsular tension ring as intraoperative measure to reduce zonular stress. One should be aware about delayed spontaneous dislocation of IOL with capsular bag years after uncomplicated cataract surgery in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In eyes with PEX, zonular weakness is a well-described clinical feature [2,4,11,12] , and there is a dehiscence of the zonular fibers noted histologically [1]. In addition, the zonules in these eyes become weak due to a degenerative process at the interface of the ciliary processes [13].…”
Section: Discussionmentioning
confidence: 99%